2013
DOI: 10.1159/000353980
|View full text |Cite
|
Sign up to set email alerts
|

Successfully Treated Abdominal Pregnancy Causing Hemoperitoneum Using Combined Surgical and Systemic Methotrexate Therapy: A Case Report and Review of Cases Treated at Kyushu University Hospital

Abstract: Abdominal pregnancy is a rare condition that accounts for only 1% of all ectopic pregnancies but results in high maternal morbidity and mortality. We present a case of abdominal pregnancy with massive peritoneal bleeding successfully treated using systemic methotrexate (MTX). A 34-year-old woman with amenorrhea for 8 weeks and a positive pregnancy test was referred for evaluation of ectopic pregnancy. Transvaginal ultrasonographic scan showed a gestational sac measuring 25 mm in diameter containing a viable em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Combined surgical and systemic MTX treatment has been successfully used in a case of abdominal pregnancy causing hemoperitoneum. Moreover, MTX may avoid the risk of excessive bleeding by surgical resection of the implantation site [73]. Nevertheless, MTX (20 mg intramuscular injection daily for 5 consecutive days) has proved to be successful in nonruptured retroperitoneal EP before operation [74].…”
Section: Discussionmentioning
confidence: 99%
“…Combined surgical and systemic MTX treatment has been successfully used in a case of abdominal pregnancy causing hemoperitoneum. Moreover, MTX may avoid the risk of excessive bleeding by surgical resection of the implantation site [73]. Nevertheless, MTX (20 mg intramuscular injection daily for 5 consecutive days) has proved to be successful in nonruptured retroperitoneal EP before operation [74].…”
Section: Discussionmentioning
confidence: 99%
“…There is limited definitive data on the effect of intramuscular methotrexate as a treatment for omental implants. Several cases studies suggest that treatment with methotrexate can prevent sudden haemorrhagic shock and that it is a safe treatment option [ 5 , 17 ]. Bora et al suggest that post-operative methotrexate can reduce the proportion of patients with persistent trophoblastic tissue following salpingostomy from 15% to 2% and would arguably reduce the rates of omental trophoblastic implants that result in acute haemoperitoneum [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…If the placenta is left in situ, it may be managed expectantly or the patient may be given MTX. Yasutake et al [21] reported a review from their own institution of the treatment of abdominal pregnancies with systemic MTX and observed that it was safe and avoided the excessive bleeding that may accompany surgical removal of the implantation site. In this review, the use of MTX was associated with higher incidences of intra-abdominal abscess formation (66.7%).…”
Section: Discussionmentioning
confidence: 99%